Challenges and Opportunities for the Use of Asphalt Mix Prepared with Ceramic Solid Waste in Emerging Countries - SOLARTE VANEGAS, Norma Cristina Cristina; GARCÍA GARCÍA, Alfredo; SERRANO GUZMÁN, Maria Fernanda; PÉREZ RUÍZ, Diego Dario (Engineering Transactions, 2024)
This research demonstrates the feasibility of using ceramic waste as a substitute for aggregates in asphalt mixtures prepared with locally available materials in Spain and Colombia. To achieve this, the asphalt mixtures were prepared following the design standards, test methods, practices, and specifications associated with quality assurance for asphalt materials. Test specimens were prepared using 30% and 35% ceramic waste as a substitute for aggregates. The results indicate that when the aggregates and binder meet the quality standards required for asphalt mixture design, the inclusion of classified ceramic waste as recycled aggregate, despite being considered inappropriate or critical material, provides mechanical benefits to the tested mixtures. As a result, this study provides relevant information to companies engaged in asphalt mix production, highlighting potential business opportunities in adopting such technological initiatives. Additionally, taking advantage of tax exemption policies established to incentivize environmentally sustainable practices can further enhance the feasibility and attractiveness of these initiatives.